2014
DOI: 10.1039/c4ra09550b
|View full text |Cite
|
Sign up to set email alerts
|

Switchable synthesis of 2,5-dimethylfuran and 2,5-dihydroxymethyltetrahydrofuran from 5-hydroxymethylfurfural over Raney Ni catalyst

Abstract: Switchable synthesis of 2,5-dimethylfuran and 2,5-dihydroxymethyltetrahydrofuran was achieved over Raney Ni catalyst, which has high feasibility in industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 35 publications
5
88
0
Order By: Relevance
“…20 Besides, 2,5-HeD was formed over NiAl-850 and NiAl-750 catalysts. Among the catalysts, NiAl-850 exhibited the highest DMF yield of ~91.5% while NiAl-300 showed the lowest DMF yield of ~44.6%.…”
Section: Synthesis Of Dmf By Hmf Hydrogenationmentioning
confidence: 93%
See 3 more Smart Citations
“…20 Besides, 2,5-HeD was formed over NiAl-850 and NiAl-750 catalysts. Among the catalysts, NiAl-850 exhibited the highest DMF yield of ~91.5% while NiAl-300 showed the lowest DMF yield of ~44.6%.…”
Section: Synthesis Of Dmf By Hmf Hydrogenationmentioning
confidence: 93%
“…9 After this work, studies Scheme 1 Hydrogenation of HMF to various products. In our previous work 20 , a switchable synthesis of DMF and DHMTHF was achieved with high yield respectively over Raney Ni, demonstrating high feasibility of Ni-based catalyst. However, the availability and high price greatly hindered the commercial applications of noble metals.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…11,17,[22][23][24][25][26]28 RANEY®-type metals (Cu, Co and Ni) have been investigated as catalyst for total hydrogenation of HMF using 1,4-dioxane as solvent by Kong et al 25 Among the RANEY®-type metals, RANEY® Ni was revealed to be the most selective with a 96% DHMTHF selectivity at full conversion, at 100 C and 15 bar of H 2 aer 15 h of reaction. 25 RANEY® Ni has also been successfully used to catalyse the hydrogenation of HMF into DHMTHF in other solvents such as methanol or ethanol with yields higher than 95%. 11,26 The best result was reported by Connolly et al using methanol as solvent, achieving 99% selectivity to DHMTHF and over 95% HMF conversion under relatively mild reaction conditions, 60 C under 4.8 bar of H 2 aer 4 h of batch operation.…”
Section: -22mentioning
confidence: 99%